The attitude of the scientist to religion and science in modern Society - Aminova Nargiza Sharifovna (Researchparks Publishing, 2021)
This article provides information on Bacon's philosophy, theoretical and practical views of the scientist on radical reform, the expediency of a progressive relationship with religion, the specificity of nature and scientific knowledge, the limits of human consciousness, political and scientific views on the balance of empiricism and theory.